Coculture of aquatic animals and paddy in brackish water: Evaluation of the growth of daily growth and morphometrics of tilapia (Oreochromis niloticus) as a fed species - Heriansah, Heriansah; Kabangnga, Arnold; Nursida, Nur Fajriani; Renal, Renal; Alfarifdi, Muh. Izzul (Universitas Malikussaleh, 2023)
A study on the cultivation of tilapia (Oreochromis niloticus) in brackish water using co-culture systems (polyculture, IMTA-non paddy, and IMTA-paddy) and monoculture systems was evaluated on a laboratory scale to determine its growth. Several species of aquatic animals and paddy (floating system) were combined with tilapia reared in plastic tanks for 28 days. Tilapia were fed four times a day at a feeding rate of 10% of biomass. The highest specific growth rate (SGR), IMTA-paddy system (4.24±0.08% day-1), polyculture (4.13±0.06% day-1), IMTA-non paddy (3.84±0.23% day-1), and monoculture (3.80±0.05% day-1). The same pattern was found in the addition of morphometric characteristics (AMC). Total length, standard length, body length, and height respectively from the highest IMTA-paddy system (2.49±0.12; 2.14±0.12; 1.81±0.14; 0.49±0.19 g), polyculture (2.32±0.16; 2.07±0.09; 1.72±0.11; 0.41±0.11 g), IMTA-non paddy (2.18±0.12; 1.78±0.15; 1.62±0.15; 0.33±0.14 g), and monoculture (2.02±0,09 1.67±0.08; 1.57±0.08; 0.30±0.10 g). Analysis of variance indicated that SGR and AMC of tilapia were significantly influenced by the culture system (P<0.05). The SGR and AMC in the IMTA-paddy system were significantly higher (P<0.05) than those in the monoculture and IMTA-non-paddy systems, but not significantly different (P>0.05) from those in the polyculture system. In general, tilapia growth was higher in co-culture systems than in monoculture systems in brackish water, which led to the diversification of aquaculture production.Keywords: Brackish water; Co-culture; Growth; Nile tilapia; Rice.